How the Hippies Saved Physics: Science, Counterculture, and the Quantum Revival by David Kaiser - Josephson, Brian (Journal of Scientific Exploration, 2012)
Kaiser’s thesis is that quantum information science, which is beginning to have application to subjects such as cryptography, came into existence only as a result of the activities of a counterculture movement, or “hippies.” The curiously ambiguous nature of the connection between the mathematics of quantum theory, and reality as observed, had led the founders of the theory to an interest in deeper issues, but the budget cuts of the Cold War period led to a more exclusive focus on practical aspects, as epitomized in the instruction “shut up and calculate!” Dissatisfied with this restriction in what one was supposed to spend one’s time thinking about, a group of people centered on the Berkeley campus of the University of California got together to form the “Fundamental Fysiks Group.”